Academic Senate Minutes 2008-03-20 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 2/21/08 approved. Revision to the German minor approved. Revision to the Psychology Major approved. Update on WASC. Chair-Elect Report and recommendation for faculty for Dean Leeder review. Questions for the Provost. University 150 approved. Course Outline Policy referred back to FSAC. RTP policy revision discussion in Committee of the Whole – no conclusion. Ad-Hoc Committee Business: Diversity. Master Course Catalog Form change approved.